Born the Opposite Sex: Classroom Exercise on Sex, Gender, and "Doing Gender" - Aronson, Pamela (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this classroom exercise, students are challenged to envision that they have been born the opposite sex. As they apply sociological concepts to their own lives, they are able to effectively understand and disentangle the distinction between sex and gender, as well as the ways that we "do gender" in our everyday interactions.